Acute and chronic urinary tract infections – diagnostics and treatment - Przybyła, Jacek; Sosnowski, Marek (Przewodnik Lekarza/Guide for GPs, 2008)
Urinary tract infections involve confirmed presence of microorganisms, which cause inflammation of the urinary tract mucosa. They also include interstitial infections: nephritis or cystitis affecting the bladder wall. The most common bacterial pathogens include: Escherichia coli (up to 90% of infections), Klebsiella, Enterococcus, Staphylococcus saprophyticus. Among hospital infections, Escherichia coli is predominant. Other bacteria include: Acinetobacter, Pseudomonas areuginosa, Serratia, Providencia. The symptoms of lower urinary tract infections include pollakiuria, urgency, hypogastric pains, and itching sensations inside the urinary bladder, or in the urethra during miction. They may also be accompanied by elevated body temperature. In the case of upper urinary tract infections, the patient may report, either in addition to the aforementioned signs, or separately, aggravation of such symptoms as pains in the lumbar region and vomiting. Urine culture is the test confirming the presence of an infection. Laboratory investigations include urine culture, urinalysis, white blood cell count, CRP, urea and creatinine levels. Imaging diagnostics consists of ultrasound scan of the urinary tract, X-ray of the abdominal cavity, and often also urography, miction cystography and ureterography. Among many different classifications of infections, the most important are differentiations between those of the lower and upper urinary tract, acute and recurrent, and simple and complicated.